The Performance Evaluation of Family Education Working Group in Education Office - Suseno, Imam (LPPM Undiksha, 2020)
This study aimed at evaluating the performance of the Family Education Working Group of Education Office in Indonesia to oversee the implementation of the family education program. The research method applied a program evaluation through an analysis of policy stage formulation to the implementation of programs specified in government policy. Using primary data, which was collected by researchers through several instruments, namely: (1) filling sheet in the form of inventory checklist, (2) in-depth interviews, and (3) documentation analysis. The results of data analysis showed that the performance of the family education working group showed a positive results, as seen in the results of mentoring in the education unit more than half of the education units including family education program in the school program and class activities agenda.